Method for extracting and purifying licorice morin - LI YUSHAN (2015)
The invention provides a method for extracting and purifying licorice morin, and the method comprises the following steps: 1) CO2 supercritical extraction of licorice morin; 2) acid dissolution and filtering of extract; 3) adsorption with macroporous adsorption resin, and elution with ethanol; 4) condensation of an ethanol eluate; and 5) drying and shaping, making into dry powder, and preparing and obtaining the licorice morin.